TAX REFORM IN THE PERFORMANCE OF TAX OFFICERS AND ITS IMPLICATIONS ON TAX COMPLIANCE IN THE PERCEPTION OF TAX PAYERS? - Kwarto, Febrian; Yunaenah, Nenah (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2019)
Many complaints submitted to tax authorities have an impact on taxpayer compliance in carrying out their obligations, while also creating opportunities for non-compliance in applicable tax regulations. This study aims to determine how much influence tax reforms have on the performance of tax service officers and its implications for taxpayer compliance according to taxpayer perceptions. The data collection instrument used in this study is a questionnaire administered to 372 corporate taxpayer respondents at the Pratama Kelapa Gading Tax Office using the convenience sampling method. The analytical tool used is the Structural Equation Model (SEM) using the LISREL (Linear Structural Relationship) program. The results of this study show that according to the taxpayers' perception, tax reform has a significant influence on tax service performance, tax service performance has a significant influence on taxpayer compliance and tax reform has a significant influence on tax compliance.